2020
DOI: 10.46690/capi.2020.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of methane adsorption and desorption in water-bearing shale

Abstract: Methane adsorption and desorption in shale can significantly be affected by water due to the water-bearing depositional environment of shale and the application of hydraulic fracturing technology in shale gas production. The characteristics of shale gas adsorption and desorption are comprehensively affected by the temperature, pressure, and especially, the water content in the reservoir. To further explore the impact of water on shale gas adsorption and desorption, the adsorption-desorption experiments of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The relationship between TOC values and V L is presented in Figure 7a, showing an evident positive correlation between the two key parameters, which is consistent with previous studies based on limited data [24,27,53]. The findings indicated that a positive correlation still exists, even when the data become larger.…”
Section: Effect Of Toc On Adsorption Capacitysupporting
confidence: 89%
See 2 more Smart Citations
“…The relationship between TOC values and V L is presented in Figure 7a, showing an evident positive correlation between the two key parameters, which is consistent with previous studies based on limited data [24,27,53]. The findings indicated that a positive correlation still exists, even when the data become larger.…”
Section: Effect Of Toc On Adsorption Capacitysupporting
confidence: 89%
“…The TOC is the most critical parameter for the shale gas reservoir evaluation. The abundance, type, and thermal maturity of OM are key factors affecting shale gas generation and enrichment [27]. The TOC not only affects the absorbed gas content of shales, but also affects the free gas content because a large number of pores are developed in OM in marine shales, which are well preserved during the process of gas generation, becoming the main storage space of shale gas [40].…”
Section: Effect Of Toc On Adsorption Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Shale gas is an important energy resource, and it is mainly stored with free gas and adsorbed gas in shale reservoirs, with adsorbed gas accounting for 20~85% [1,2]. The shale gas reservoir usually has low permeability and low porosity.…”
Section: Introductionmentioning
confidence: 99%
“…The shale gas reservoir usually has low permeability and low porosity. Generally, the shale matrix porosity is less than 10%, and its permeability is approximately 10 −5 mD [1]. Meanwhile, it has high organic matter content, rich nano-pores, and large specific surface area, which are favorable for methane adsorption, as the main component (more than 95%) of shale gas [3][4][5].…”
Section: Introductionmentioning
confidence: 99%